1994
DOI: 10.1111/j.1600-051x.1994.tb00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Nd:YAG laser and combined treatments on in vitro fibroblast attachment to root surfaces

Abstract: The purpose of this in vitro study was to evaluate the effects of the Nd:YAG laser either alone or in combination with root planning or air-powder abrasive treatment on fibroblast attachment to non-diseased root surfaces. 28, 4 x 4 mm root specimens and four disc-shaped root specimens 6 mm in diameter were obtained from unerupted 3rd molars. The root segments were randomly assigned to 4 treatment groups: (1) control; (2) laser-only treated; (3) laser treated followed by root planning; (4) laser treated followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 24 publications
(7 reference statements)
2
39
1
2
Order By: Relevance
“…The American Academy of Periodontology, in its position statement on lasers in ENAP, 15 states 'The Academy is not aware of any published data that indicates that the ENAP laser procedure is any more effective for these purposes than traditional scaling and planing'. 12,[16][17][18][19][20][21][22] This is sharply contrasted by reports by Gregg and McCarthy, reported in later journals. [23][24][25] In 2004 in a study presented by Evans 26 to review the new attachment procedure on a sample of six cases, evidence was given to show new cementum and bone growth, including periodontal ligament.…”
Section: De-epithelialisation Of the Periodontal Pocketcontrasting
confidence: 55%
“…The American Academy of Periodontology, in its position statement on lasers in ENAP, 15 states 'The Academy is not aware of any published data that indicates that the ENAP laser procedure is any more effective for these purposes than traditional scaling and planing'. 12,[16][17][18][19][20][21][22] This is sharply contrasted by reports by Gregg and McCarthy, reported in later journals. [23][24][25] In 2004 in a study presented by Evans 26 to review the new attachment procedure on a sample of six cases, evidence was given to show new cementum and bone growth, including periodontal ligament.…”
Section: De-epithelialisation Of the Periodontal Pocketcontrasting
confidence: 55%
“…38,[46][47][48][49][50][51][52][53][54] Studies with Nd:YAG laser using different parameters 47,48 have shown that mean power settings ranging between 1.25-3.00 W promote a root surface change leading to fusion and resolidification of the cement mineral portion alongside crack and fissure formation. Thomas et al 46 reported that the Nd:YAG laser denatures root surface proteins, and they suggest that the complement of the conventional mechanical treatment of the root surface would be important on the reduction of these irregularities aiming for a more biocompatible root surface. Meanwhile, Trylovich et al 49 found that Nd:YAG laser application modifies biocompatibility of root surfaces and reduces the number of attached fibroblasts in comparison with untreated controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, potential detrimental effects to the root surface could occur if the irradiation conditions are not controlled well [24][25][26]. In contrast to many studies on structural change of hard tissue, the effect of Nd:YAG laser on soft tissue need more investigation.…”
Section: Discussionmentioning
confidence: 99%